Sustained censorship in TR (2026-03) (Turkey) - Voidly (2026)
CRITICAL severity censorship detected in Turkey. Confidence: 72%. Data sourced from OONI.
Censorship Incident ID: TR-2026-0124
Keywords: censorship; TR; censorship; critical